The effect of fixture congestion on performance during professional male soccer match-play: A systematic critical review with meta-analysis - Julian, R.; Page, R. M.; Harper, L. D. (Sports Medicine, 2021)
Background: Fixture congestion (defined as a minimum of two successive bouts of match-play, with an inter-match recovery period of < 96 h) is a frequent and contemporary issue in professional soccer due to increased commercialisation of the sport and a rise in the number of domestic and international cup competitions. To date, there is no published systematic review or meta-analysis on the impact of fixture congestion on performance during soccer match play.